Effect of time and day of admission on hospital care quality for patients with chronic obstructive pulmonary disease exacerbation in England and Wales: single cohort study. Issue 9 (6th September 2017) - Roberts, Christopher Michael; Lowe, Derek; Skipper, Emma; Steiner, Michael C; Jones, Rupert; Gelder, Colin; Hurst, John R; Lowrey, Gillian E; Thompson, Catherine; Stone, Robert A
Abstract : Objective: To evaluate if observed increased weekend mortality was associated with poorer quality of care for patients admitted to hospital with chronic obstructive pulmonary disease (COPD) exacerbation. Design: Prospective case ascertainment cohort study. Setting: 199 acute hospitals in England and Wales, UK. Participants: Consecutive COPD admissions, excluding subsequent readmissions, from 1 February to 30 April 2014 of whom 13 414 cases were entered into the study. Main outcomes: Process of care mapped to the National Institute for Health and Care Excellence clinical quality standards, access to specialist respiratory teams and facilities, mortality and length of stay, related to time and day of the week of admission. Results: Mortality was higher for weekend admissions (unadjusted OR 1.20, 95% CI 1.00 to 1.43), and for case-mix adjusted weekend mortality when calculated for admissions Friday morning through to Monday night (adjusted OR 1.19, 95% CI 1.00 to 1.43). Median time to death was 6 days. Some clinical processes were poorer on Mondays and during normal working hours but not weekends or out of hours. Specialist respiratory care was less available and less prompt for Friday and Saturday admissions. Admission to a specialist ward or high dependency unit was less likely on a Saturday or Sunday. Conclusions: Increased mortality observed in weekend admissions is not easily explained by deficiencies in early clinical guideline care. Further study of out-of-hospital factors, specialty care and deaths later in the admission are required if effective interventions are to be made to reduce variation by day of the week of admission.